ANALISIS FORMULA â€œDIARI KAMBING JANTANâ€ KARYA RADITYA DIKA - Astika, I Made (Universitas Pendidikan Ganesha, 2014)
The purpose of the paper is to describe the formulas found in Kambing Jantan diary. The employed approach is textual analysis. The data unit is in form of the text collected by documenting method. The data is analyzed by explaining, comparing, relating, sorting, or combining with popular literary theory. From the previously completed analysis, Kambing Jantan diary has several formulas to construct itself as a comedy novel. The formulas are deployed in the diction (use of language), the topic of discussion selection, and the behavior of the characters. The type of humor is personal humor. By the use of bombastic slang, Kambing Jantan becomes a favorite kind of the new among the readers. In relation to this, the humor that is offered in Kambing Jantan tends to present itself as its function as a means of entertainment.Keywords: formula, humor, comedy, diary